2023
DOI: 10.3390/vetsci10020108
|View full text |Cite
|
Sign up to set email alerts
|

Gray Wolf (Canis lupus italicus) and Red Fox (Vulpes vulpes) Parasite Survey in Anthropized and Natural Areas of Central Italy

Abstract: Gastrointestinal nematodes and protozoa and other parasite occurrences were evaluated in free-ranging wolf (Canis lupus italicus) and red fox (Vulpes vulpes) populations from natural and anthropized areas of Central Italy. Analyzed fecal samples were collected from 60 foxes and 40 wolves in the anthropized areas, and 41 foxes and 39 wolves in the natural areas. In foxes, hookworm infections (p < 0.0001) were more frequently recorded in the anthropized environment, while coccidia (p < 0.05) and Cryptospor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…A recent study from Italy reported the presence of Neospora/Hammondia spp. oocysts in only one fecal sample (1.3%) [43], while in Croatia their presence was confirmed for 2.6% fecal samples using non-molecular coprological methods [44]. Both studies could benefit from the use of molecular methods to determine the prevalence of N. caninum in their samples.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study from Italy reported the presence of Neospora/Hammondia spp. oocysts in only one fecal sample (1.3%) [43], while in Croatia their presence was confirmed for 2.6% fecal samples using non-molecular coprological methods [44]. Both studies could benefit from the use of molecular methods to determine the prevalence of N. caninum in their samples.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, human-induced environmental changes increase the incidence of diseases, notably zoonotic infections, with approximately 61% of human pathogens being zoonotic and 71.8% of emerging human diseases originating from wildlife [ 11 , 12 , 13 , 14 ]. Concurrently, the process of spillback or zooanthroponosis complicates wildlife conservation efforts, presenting a novel concern about transmission of pathogens from humans to wild animals [ 15 ].…”
Section: Introductionmentioning
confidence: 99%